STUDENTS PHYSICAL FITNESS LEVEL WHO FOLLOWING PENCAK SILAT IN BUDI MULIA DUA ELEMENTARY SCHOOL - Ariyati Pangestuti; Siswantoyo Siswantoyo (Jorpres (Jurnal Olahraga Prestasi), 2016)
This research aims to know the level of students' physical fitness in grade IV and V of Budi Mulia Dua Elementary school who following Pencak Silat.This is a descriptive research. The population is all (220 students) the students of grade VI and V in Budi Mulia Dua Elementary school. The sample was taken 35% from all population (72 students), proportionate strattfied random sampling was used in this research. The technique of taking the data was used measurement test. The instrument used was Indonesian Physical Fitness Test year 2009 age 10-12 years old. Data analysis technique was using percentage descriptive.The result showed that the level of students physical fitness in grade IV and V of Budi Mulia Dua Elementary school who following pencak silat got 15 students (20.83%) belong to very poor categorry 36 students (50%) belong to poor category 16 students (22.22%) belong to fair categorry and 5 students (6.94%) belong to good category. If see from the gender, from 36 female students, 6 students (16.67%) belong to very poor categorry 18 students (50%) belong to poor categofYr 9 students (25%) belong to fair category and 3 students (8.33%) belong to good category. From 36 male students, 9 students (25%) belong to very poor categorry 18 students (50%) belong to poor categorry 7 students (19.44%) belong to fair category and 2 students (5.56%) belong to good category. If see from each class, from 36 students of grade VI, 6 students (16.67%) belong to fait categorry 21 students (58.33%) belong to poor category and 9 students (25%) belong to very poor category. From 36 students of grade V, 5 students (13.89) belong to good categorry 10 students (27.78%) belong to fair categorry 15 students (41.67%) belong to poor categofYr and 6 students ( 16.6 7%) belong to very poor category. Generai!Yt it can be concluded that 50% from 72 students grade IV and V of Budi Mulia Dua Elementary school who follow Pencak Silat in the poor level category. Keywords: physical fitness level, students, local lesson